2022
DOI: 10.51470/plantarchives.2022.v22.no1.013
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE GENETIC VARIABILITY FOR VARIOUS AGRONOMIC TRAITS OF PEA (Pisum sativum L.) GENOTYPES

Abstract: The present study was conducted to study genetic variability and association among agronomic characters of pea (Pisum sativum L.) genotypes. The field experiment was conducted using ten genotypes at College of Agricultural Sciences (CAS) of International University of Business Agriculture and Technology (IUBAT), Dhaka, Bangladesh during the Rabi season (November 2020 to March 2021). Treatments were using the randomized complete block design (RCBD) with three replications. Highly significant (p ≤ 0.01) differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our observations indicate that maximum SN is equal to the ON and achievable only in a small fraction of pods (S/O = 1.00). Those authors who studied the impact of average (not maximum) SN on productivity found them correlating significantly [6,9].…”
Section: Ovule Number Is a Relatively Variable Trait Weakly Correlate...mentioning
confidence: 99%
See 3 more Smart Citations
“…Our observations indicate that maximum SN is equal to the ON and achievable only in a small fraction of pods (S/O = 1.00). Those authors who studied the impact of average (not maximum) SN on productivity found them correlating significantly [6,9].…”
Section: Ovule Number Is a Relatively Variable Trait Weakly Correlate...mentioning
confidence: 99%
“…Only relatively strong (r > 0.5) and statistically significant correlations are discussed below. The seed yield in pea (i.e., mass of seeds produced by a single plant or a plot) was found predictably correlated with primary components of productivity, such as number of seeds [5,9] and pods [4][5][6] per plant or, to a surprisingly lesser extent, number of seeds per pod [3,6,9,10]. Data on the impact of 1000 seed mass on a yield are contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A valuable resource that contains a vast amount of genes that are desirable for crop improvement is the germplasm repository, however, this can only be used with an understanding of the extent of genetic diversity [14]. A wide range of methods involving the measurement and analysis of morphological characteristics have been employed to evaluate and categorize different genotypes across various crop species, including alfalfa, cowpea, lentil, soybean, mustard, peas, and mungbean [15][16][17][18][19][20]. The assessment of genetic diversity can be carried out by evaluating both qualitative and quantitative traits.…”
Section: Introductionmentioning
confidence: 99%